State program for reducing the consequences of war and improving the health of the disabled - Berezutskyi, Viacheslav; Khalil, Rita (Національний технічний університет "Харківський політехнічний інститут", 2023)
Urgent state projects of programs to reduce the consequences of war and to improve the health of the disabled are being considered. The relevance of this issue has not decreased for more than 10 years in Ukraine, and now it is increasing due to the war.

Розглядаються нагальні державні проєкти програм щодо зменшення наслідків війни та покращення здоров'я інвалідів. Актуальність цього питання неспадає вже більше 10 років в Україні, а зараз зростає через війну.
Державна програма зменшення наслідків війни та покращення здоров'я інвалідів
Keywords: projects of state programs; consequences of the war; disabled people; державні проєкти програм; наслідки війни; інваліди